Being Willing but Not Able: Echoes of Intimate Partner Violence as a Hindrance in Women’s Desistance from Crime - Gålnander, Robin (Journal of developmental and life-course criminology, 2019)
Purpose: This article emphasizes the complexity of desistance processes by exploring how echoes of violent victimization from intimate partners work as a hindrance or barrier to desistance. Drawing on interviews with women who are striving to desist, this article seeks to elucidate how past experiences of excessive and recurring violent victimization affect the life course, with a focus on their restrictions on the women’s desistance processes. Methods: This paper is built upon repeated qualitative interviews with ten women in the early stages of their desistance processes. They were all interviewed repeatedly on a 6-monthly basis for 2 years. Echoes of violent victimization as a hindrance to desistance emerged as a theme during the interviews and are explored further via a thematic analysis. Results: Echoes of violent victimization from intimate partners restrict the women’s social lives, complicating an already fragile (re)connection to conventional society. Additionally, many of the women are restricted by post-traumatic stress disorders directly related to their violent victimization, which impedes their agency and limits their abilities to act towards desistance. Conclusions: Recurring violent victimization has severe implications for the women’s desistance processes. Both social and health-related consequences of this violence restrict the women’s ability to act towards desistance from crime and expose them to painful experiences of isolation, goal failure, and hopelessness. These conclusions are important contributions to the understanding of the complexity of desistance processes.